A Review On Indoor Smart Energy Management System - Li, Woon Koay; Hashim, Yasir (Penerbit Universiti Malaysia Pahang, 2017)
One of the best to reserve energy is converted the original home into an intelligent one or known as “Smart Home”. In this paper, a review on smart energy management system was presented. Various novel methods and technologies are being extensively explored.